AN ANALYSIS OF THE STUDENTS’ MOTIVATION TOWARD ENGLISH LEARNING IN ONLINE CLASSES - Wahyuni, Eka Putri; Rezeki, Yanti Sri; Wardah, Wardah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
The purpose of this research is to describe the students’ motivation toward English learning in online classes and investigate the types of motivation of the students. The data in this study were collected through questionnaires and interviews. The participants in this study were 125 students of the English Language Education Study Program, Universitas Tanjungpura, batch 2020 and 2021, REG A and PPAPK class. The research findings revealed, that most of the students of the English Language Education Study Program, Universitas Tanjungpura, batch 2020 and 2021 have a high level of motivation toward English learning in online classes on both types of motivation, intrinsic and extrinsic. The research findings showed that 94% of students are categorized as students with a high level of motivation, and the other 6% are categorized as students with a low level of motivation. Specifically, students are more extrinsically motivated than intrinsically with a total mean score for extrinsic motivation is 2.95 and for intrinsic motivation is 2.57. Several factors were found to influence students to have extrinsic and intrinsic motivation such as cost-effectiveness, accessibility, environment, career, facility, confidence, personal enjoyment, need, and preference. The findings of this research suggest pedagogical implications.